Are Recipients of Social Assistance 'Benefit Dependent'? Concepts, Measurement and Results for Selected Countries - Herwig Immervoll; Stephen P. Jenkins; Sebastian Königs (Institute for the Study of Labor (IZA), 2015)
Means-tested Social Assistance (SA) benefits play an important role as social protection floors supporting households in financial difficulties. This paper presents evidence on the patterns of SA benefit receipt in a selection of OECD and EU countries. It provides an overview of the role of SA benefits in social protection systems and assesses the generosity of benefit payments. It then studies the dynamics of SA benefit receipt based on micro-level data describing trends in aggregate receipt and transition rates and presenting new evidence on spell durations and repeat spells. The final part of the paper summarizes recent empirical evidence on state dependence (or 'scarring effects') in benefit receipt and discusses its possible sources and policy implications.
Keywords: I38; J60; J64; C23; 330; social assistance; welfare benefits; state dependence; benefit dependence; scarring